Ecological Sustainability of Leaching and N Utilisation in Solanum Lycopersicum Var. Cerasiforme Via Green Synthesis of Zeolite LTA - Norsuhailzah Sazali; Zawati Harun; Norazlianie Sazali; Afdhal Junaidi, (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
A sustainable green synthesis of zeolite from kaolin was incorporated into loam to reduce leaching and improve environmental sustainability. This research determined the effects of a cation-binding mineral zeolite on nitrogen leaching, nitrogen absorption, and cherry tomato yield in pots. There are seven distinct experimental handlings: Control High (CH); Control Attainment (CS); Control Low (CL); 2g of zeolite(2gZ); 4g of zeolite(4gZ); 6g of zeolite(6gZ); and 6g of commercial zeolite (6gIZ) grown in a greenhouse. A design replicated 30 times. The implementation of the Least Significant Difference (LSD) post-hoc test (P≤0.05) enables the effectiveness measurement of all loam handlings towards leaching and N utilisation in loam. According to the results, 6g of zeolite shows the smallest, highly significant difference in the mean concentrations of nitrite and nitrate compared with the other handlings (p < 0.05). Regarding the average nitrogen concentration in the loam at each harvest, the 6 g zeolite handling distinctly increased the average loam nitrogen concentration compared to other handlings (p < 0.05). There was no statistically significant difference in fruit mass between handlings (p > 0.05); however, the handling with 6 g of zeolite produced the highest mean fruit mass overall. In conclusion, with the zeolite capacity expressed as Cation exchange capacity (CEC), this green-synthesised zeolite reduced water discharge from a container while increasing the average nitrogen concentration in the loam.